2005
DOI: 10.1097/01.mpg.0000154662.39488.77
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Status and Symptom Assessment Two Years after Eradication in Pediatric Patients from a High Prevalence Area

Abstract: The 12.8% per year reinfection rate in childhood at 2 years that we observed should prompt a re-evaluation of H. pylori status even after a successful eradication. Living in an H. pylori high prevalence area increases the annual risk of reinfection by approximately fourfold over the annual risk in H. pylori low prevalence areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 36 publications
2
34
2
Order By: Relevance
“…Only four articles have reported on the risk factors associated with reinfection in childhood [19][20][21]23]. Consistent with the findings of Rowland et al [19] our data did not show that the risk of reinfection depended on the age of the index child, number of siblings, low socioeconomic status, or living conditions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Only four articles have reported on the risk factors associated with reinfection in childhood [19][20][21]23]. Consistent with the findings of Rowland et al [19] our data did not show that the risk of reinfection depended on the age of the index child, number of siblings, low socioeconomic status, or living conditions.…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, only five studies are reported on reinfection rate and risk factors of reinfection in childhood [19][20][21][22][23], and there are few data on the long-term efficacy of treatment in children. To our knowledge, only five studies are reported on reinfection rate and risk factors of reinfection in childhood [19][20][21][22][23], and there are few data on the long-term efficacy of treatment in children.…”
mentioning
confidence: 99%
“…22 In the present study, vomiting was significantly higher in H. pylori infected children than in non-infected ones (24.04% versus 8.6%, p=0.001). 15,30,40 However, we did not find any significant difference in the incidence of nausea, 37 or diarrhea. 35 Other studies reported positive association between diarrhea and H. pylori infection in children.…”
Section: It Is Not Yet Clear Whether the Difference In Anthropometry contrasting
confidence: 54%
“…Epigastric pain as a localizing symptom associated with H. pylori infection has been documented in other studies as well. 6,[35][36][37] However, epigastric pain was less frequently encountered in the study by Kalach et al 38 Upper GI endoscopy and biopsy was carried out in 10 children with persistent epigastric pain and vomiting. It revealed a significantly higher incidence of nodular gastritis in H. pylori infected cases especially among older children (p<0.05), and indicates histopathological evolution of the lesions with chronicity of infection.…”
Section: It Is Not Yet Clear Whether the Difference In Anthropometry mentioning
confidence: 99%
“…A large body of evidence shows that the prevalence of H. pylori was significantly higher among children with reflux oesophagitis than in children with hyperemic gastropathy [31] . However, we could not find any significant difference between H. pylori positive and negative cases in the incidence of nausea, and vomiting [32] , or diarrhea [33] . However, other studies reported positive correlation between the infection and diarrhea [3,18] , and in some cases it correlates with vomiting [3] .…”
Section: Patientsmentioning
confidence: 45%